Phytochemical intervention for lymphatic filariasis and filarial lymphedema - Bonnah, Rose; Ayisi, Felix; Wireko, Solomon; Kwarteng, Alexander (Frontiers in Tropical Diseases, 2023)
Filarial lymphedema is a chronic pathophysiological condition initiated by parasitism by lymphatic filarial worms. Although the disease is not immediately fatal, it is a significant social and economic issue, particularly in sub-Saharan Africa. Given the ongoing need for effective therapeutic strategies for filarial lymphedema, several countries have turned to natural products and herbal interventions as promising source for developing anti-filarial agents to manage lymphatic filariasis (LF). This review aims to classify various plant molecules implicated in treating LF, with a focus on their anti-filarial properties. This information can be used to further investigate their efficacy in managing filarial lymphedema.